CONTRIBUTION TO THE STUDY OF THE NOCTUIDAE OF ČELAREVO (SERBIA) (Acta Entomologica Serbica, 2017)
Moths were collected in Čelarevo (UTM CR81) from 2008 to 2014 using a light trap, type RO Agrobecej, with a 250W mercury lamp. A total of 234000 specimens were collected, of which 223226 are identified at species level (292 species in all). The present paper provides data relating to 28921 specimens of 137 Noctuidae species. The faunistically most important findings are as follows: Diachrysia nadeja, Diachrysia zosimi, Diachrysia chryson, Acontia candefacta, Acronicta aceris, A. strigosa, Simyra albovenosa, Cucullia fraudatrix, Amphipyra livida, Meganephria bimaculosa, Heliothis nubigera, Charanyca ferruginea, Calamia tridens, Helotropha leucostigma, Gortyna borelii lunata, Hydraecia micacea, Archanara dissoluta, Apamea anceps, Mesogona oxalina, Panolis flammea, Saragossa porosa kenderesiensis, Hadena irregularis, Senta flammea, Agrotis puta, A. vestigialis, Cerastis rubricosa.